Helicobacter pylori and its hematological effect - Yousryeia Abdel Rahman; Lobna Abdel wahid Ahmed; Rania Mohamed mahmoud Hafez; Rasha Mohamed Mahmoud Ahmed (SpringerOpen, 2019)
Background Helicobacter pylori causes several gastric, intestinal, and extraintestinal manifestations. It also causes persistent infection and can cause serious various hematological effects. Aims To investigate the hematological effect of H. pylori infection. Patients and methods This is a cohort study that included 50 adult (age range: 18-75 years) patients infected with H. pylori and 50 adult patients who presented with symptoms suggestive of gastritis. All patients underwent upper endoscopy, and biopsies were taken. Moreover, the patients underwent complete blood count, iron studies, hepatitis C virus antibodies, vitamin B12 level, and bone marrow aspirate. Result The results showed that hemoglobin level, serum iron level, vitamin B12 levels, and platelets count were much lower in patients infected with H. pylori than the control group. Conclusion H. pylori causes iron-deficiency anemia, vitamin B12 deficiency, and thrombocytopenia, and treatment of H. pylori causes much improvement in these parameters.